2020
DOI: 10.1097/inf.0000000000002759
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Zoster Reactivation Causing Aseptic Meningitis in Healthy Adolescents

Abstract: We describe 3 cases of adolescent varicella-zoster virus reactivation, complicated by aseptic meningitis, presenting to our institution in a 3-year period. These cases highlight varicella-zoster virus reactivation as an important cause of aseptic meningitis in the differential diagnosis of healthy adolescents, even in the absence of a characteristic exanthem. Evidence-based management recommendations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Although there have been substantial cases of varicella vaccine meningitis in the literature [ 2 , 6 , 7 ], our case is probably the second case of varicella vaccine meningitis without skin rash. However, VZV reactivations causing aseptic meningitis without rash associated with the past varicella infection have also been reported [ 1 , 8 ]; therefore, even in the absence of rash, in cases of aseptic meningitis, performing VZV PCR is crucial; moreover, if VZV test is positive, additional loop-mediated isothermal amplification assay [ 2 ] or metagenomic next-generation sequencing [ 7 ] for VZV to differentiate the vOka strain from the wild-type VZV strain is essential to confirm the etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been substantial cases of varicella vaccine meningitis in the literature [ 2 , 6 , 7 ], our case is probably the second case of varicella vaccine meningitis without skin rash. However, VZV reactivations causing aseptic meningitis without rash associated with the past varicella infection have also been reported [ 1 , 8 ]; therefore, even in the absence of rash, in cases of aseptic meningitis, performing VZV PCR is crucial; moreover, if VZV test is positive, additional loop-mediated isothermal amplification assay [ 2 ] or metagenomic next-generation sequencing [ 7 ] for VZV to differentiate the vOka strain from the wild-type VZV strain is essential to confirm the etiology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of aseptic meningitis in children in Ireland reported 11 cases of VZV meningitis or meningoencephalitis in immune competent children with a prior history of childhood varicella but no herpes zoster [ 38 ]; in other words, these 11 children presumably had VZV reactivation in the CNS without clinical herpes zoster ( Figure 7 ). Of interest, 10 of the 11 children were adolescents between ages 12–16.…”
Section: Varicella Meningitis Caused By Wild Type Varicellamentioning
confidence: 99%
“…None of the children had herpes zoster prior to developing meningitis. Data from reference [ 38 ]. Age of wild type varicella: green bar; age of meningitis: red bar.…”
Section: Figurementioning
confidence: 99%
“…1,2 VZV primary infection (chickenpox) normally occurs in preschool or schoolaged children.1 After the primary infection, the virus remains latent in cranial nerves, dorsal roots, and autonomic ganglia, and it may reactivate years after the primary infection as zoster. 1,3 Both chickenpox and zoster may have neurologic complications, mainly in immunocompromised or older patients. 1,3,4 Reactivation is linked to a decline in cell-mediated immunity, and so, associated with immunocompromised or older individuals, being exceedingly rare in paediatric immunocompetent patients.…”
mentioning
confidence: 99%
“…1,3 Both chickenpox and zoster may have neurologic complications, mainly in immunocompromised or older patients. 1,3,4 Reactivation is linked to a decline in cell-mediated immunity, and so, associated with immunocompromised or older individuals, being exceedingly rare in paediatric immunocompetent patients. 1,5 Pediatric reactivation cases seam to occur mainly when VZV-infection was acquired in the first year of life.…”
mentioning
confidence: 99%